PROFESSIONAL PURPOSES OF TEACHING ENGLISH TO FUTURE MASTERS OF EDUCATION MANAGERS - Zolotko, Yuliia (Continuing Professional Education: Theory and Practice, 2019)
The article studies the issue of teaching English for professional purposes. The author specifies how to design the course «Foreign language in the professional environment» for Master degree students majoring in «Management of the educational institution»; describes the educational and methodological complex of the discipline consisting of educational and working programs of the discipline, methodological guidance for practical classes and self-study work, diagnostic tools for measuring learning outcomes, a reference list of educational and methodological textbooks, technical teaching aids, information resources on the discipline. The article describes the ways of interpreting the term «foreign language for professional purposes», which is treated in the study as a set of linguistic resources used in the definite communicative sphere in order to achieve understanding between all the specialists of the particular professional area. The author analyses the roles of a teacher of a foreign language for professional purposes; suggests the algorithm of the teacher’s actions that is the most rational for designing profession-oriented learning; provides the examples of new approaches and innovative techniques. The author concludes that the most effective type of educational activity is a continuous role-play which comprises the following teaching and learning activities: case-study, brainstorming and discussions; student presentations; project work involving the students in a semester-long team educational project; searching the information (on English education websites) necessary to perform creative learning tasks such as the educational project, presentations, various discussions; writing essays: resumes, reports, articles (for a magazine or advertisement of an educational institution) aimed at summarizing the outcomes of different creative tasks.